A Web-based modeling tool for the SEMAT Essence theory of software engineering. (2nd September 2013) - Graziotin, Daniel; Abrahamsson, Pekka
As opposed to more mature subjects, software engineering lacks general theories that establish its foundations as a discipline. The Essence Theory of software engineering (Essence) has been proposed by the Software Engineering Methods and Theory (SEMAT) initiative. The goal of Essence is to develop a theoretically sound basis for software engineering practice and its wide adoption. However, Essence is far from reaching academic- and industry-wide adoption. The reasons for this include a struggle to foresee its utilization potential and a lack of tools for implementation. SEMAT Accelerator (SematAcc) is a Web-positioning tool for a software engineering endeavor, which implements the SEMAT's Essence kernel. SematAcc permits the use of Essence, thus helping to understand it. The tool enables the teaching, adoption, and research of Essence in controlled experiments and case studies.